Denitration catalyst, preparation method and low-temperature denitration process
By synthesizing nano ceria and nanomanganese dioxide in situ on the surface of graphene oxide nanosheets and forming a sandwich structure, combining the network structure of modified glass fiber and nickel foam, the active components of porous structure catalysts are easily shedded and mechanically processed. The problem of insufficient strength improves denitrification efficiency and compressive strength.
Patent Information
- Application Number
- CN202411676219.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The active components of the existing porous structure denitrification catalyst have poor binding force with the support, are prone to fall off, and are prone to breaking under the action of external forces, resulting in a decrease in denitrification efficiency.
Nanoceria and nanomanganese dioxide are synthesized in situ on the surface of graphene oxide nanosheets, and sandwich structure is formed through dopamine surface modification, increasing active sites and pore structures, and a unique network structure combining modified glass fibers and nickel foam foam is unique , enhance the compressive strength of the catalyst and the protection of the active components.
It effectively improves the activity and mechanical strength of the denitrification catalyst, extends the service life, and improves the contact area and denitrification efficiency of nitrogen oxides.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas denitration, and in particular to a denitration catalyst and a preparation method thereof, and a low-temperature denitration process. Background Art
[0002] Nitrogen oxides are collectively referred to as NO x It is one of the main sources of air pollution. The main sources include fixed sources and mobile sources. Fixed sources mainly include thermal power, glass, ceramics, cement, steel and other industries, and mobile sources mainly include motor vehicles and non-road machinery. Excessive NO x It can cause a series of environmental problems such as acid rain, ozone layer depletion and photochemical smog, and is toxic to human health and plants. Flue gas denitrification refers to the removal of NO in flue gas. x According to the treatment process, it can be divided into wet denitrification and dry denitrification. It mainly includes: acid absorption method, alkali absorption method, selective catalytic reduction method, non-selective catalytic reduction method, adsorption method, plasma activation method, etc. Among them, the selective catalytic reduction denitrification catalyst can react nitrogen oxides in flue gas with ammonia or urea, converting them into nitrogen and water to achieve denitrification effect.
[0003] The use of selective catalytic reduction denitrification catalyst to treat flue gas can effectively remove nitrogen oxides in the flue gas. Among them, the use of a porous structure catalyst to load the active components has a higher denitrification effect, but the active components have poor bonding with the porous structure of the catalyst carrier and are easy to fall off, resulting in catalyst deactivation. In addition, the porous structure of the denitrification catalyst is easily broken by external force and has poor mechanical strength, which affects the denitrification efficiency of the denitrification catalyst. Summary of the invention
[0004] The purpose of the present invention is to provide a denitration catalyst and a preparation method thereof and a low-temperature denitration process: in situ synthesis of nano-cerium dioxide and nano-manganese dioxide on the surface of graphene oxide nanosheets to avoid the shedding of active components of nano-cerium dioxide and nano-manganese dioxide, which affects the denitration performance, and to form a concave-convex structure on the surface of graphene oxide nanosheets, thereby increasing the number of active sites of the denitration catalyst; dopamine surface-modified zirconium oxide nanosheets are deposited on the surface of modified graphene oxide to form a sandwich structure, so that the active components of nano-cerium dioxide and nano-manganese dioxide are present between the interlayers, giving the interlayers a relatively high The large pore structure increases the contact area with nitrogen oxides, and the formed sandwich structure further increases the protection of the active components of nano-cerium dioxide and nano-manganese dioxide, avoiding the shedding of active components; the acid-etched glass fiber is mixed with oxalic acid and melamine, and after calcination, a large amount of evenly distributed nitrogen elements are formed on the surface of the glass fiber. The formed nitrogen elements promote the adsorption and oxidation ability of nitrogen oxides on the surface of the denitrification catalyst; the composite nanomaterials and modified glass fibers are dispersed in the unique network structure of the nickel foam, serving as the supporting skeleton of the nickel foam, thereby improving the compressive strength of the nickel foam denitrification catalyst.
[0005] The technical problem to be solved by the present invention is as follows: the use of a porous structure catalyst to load active components has a high denitration effect, but the active components have poor bonding with the porous structure catalyst carrier and are easy to fall off, resulting in catalyst deactivation, and the porous structure of the denitration catalyst is easily broken under the action of external force and has poor mechanical strength, which affects the denitration efficiency of the denitration catalyst.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a denitration catalyst comprises the following steps: S1. Mix the composite nanomaterial, modified glass fiber and deionized water, stir and obtain slurry.
[0007] S2. Impregnate the acid-treated nickel foam into the slurry, stir at 400-500 rpm for 5-6 hours, filter, wash, dry, sinter, and cool to room temperature to obtain a denitration catalyst.
[0008] Furthermore, in step S1, the ratio of the composite nanomaterial, modified glass fiber, and deionized water is (3-4) g: (1-2) g: (80-120) mL.
[0009] Furthermore, in step S2, the mass ratio of the acid-treated nickel foam to the slurry is (30-40):(50-60).
[0010] Furthermore, in step S2, the sintering temperature is 350-450°C, and the sintering time is 3-4h.
[0011] Furthermore, in step S2, the drying temperature is 70-90°C and the drying time is 1-3h.
[0012] Further, the acid-treated nickel foam is prepared by the following steps: The nickel foam was soaked in an acetone solution for 15 minutes, taken out, washed three times with deionized water, and then soaked in 3 mol / L dilute hydrochloric acid for 15 minutes, taken out, washed three times with deionized water, and dried in an oven at 60° C. for 10 minutes to obtain an acid-treated nickel foam.
[0013] Among them, acetone treatment of nickel foam can effectively remove grease, oil stains and other organic impurities on the surface of nickel foam, and dilute hydrochloric acid can react with the oxide layer on the surface of nickel foam to remove the oxide layer, which is beneficial to the mixed adsorption of nickel foam and slurry.
[0014] Furthermore, the porosity of nickel foam is 94-96%, the pore size is 0.1-0.2 mm, and the volume density is 0.4-0.6 g / cm 3 .
[0015] Furthermore, the composite nanomaterial is prepared by modifying the surface of zirconium oxide nanosheets with dopamine and then mixing them with modified graphene oxide.
[0016] Furthermore, the diameter of the zirconium oxide nanosheets is 0.1-1 μm.
[0017] Furthermore, the composite nanomaterial is specifically prepared by the following steps: A1. Add zirconium oxide nanosheets to Tris-HCl buffer with a pH of 8.5, stir evenly, add dopamine, stir for reaction, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 minutes to obtain dopamine surface-modified zirconium oxide nanosheets.
[0018] A2. The modified graphene oxide and dopamine surface-modified zirconia nanosheets were added to deionized water, ultrasonically treated at 40 Hz for 30 min, filtered, washed with deionized water three times, and dried in an oven at 80° C. for 10 min to obtain a composite nanomaterial.
[0019] Furthermore, during the above-mentioned A1 reaction, the phenolic hydroxyl structure contained in dopamine has good adhesion, and dopamine can self-polymerize in Tris-HCl buffer to form a polydopamine layer on the surface of the zirconia nanosheets, giving the zirconia nanosheets excellent adhesion, thereby obtaining dopamine-surface-modified zirconia nanosheets.
[0020] Furthermore, in the above-mentioned A2 reaction process, the surface of the dopamine-modified zirconia nanosheets contains a polydopamine layer, and the dopamine-modified zirconia nanosheets can be deposited on the surface of the modified graphene oxide to form a sandwich structure, so that the nano-cerium dioxide and nano-manganese dioxide active components on the surface of the modified graphene oxide exist between the interlayers, giving the interlayers a larger pore structure and increasing the contact area with nitrogen oxides.
[0021] Furthermore, in step A1, the ratio of the amount of zirconium oxide nanosheets, Tris-HCl buffer, and dopamine is (2-3) g: (45-55) mL: (0.5-0.9) g.
[0022] Furthermore, in step A2, the usage ratio of modified graphene oxide, dopamine surface-modified zirconium oxide nanosheets, and deionized water is (0.1-0.3) g: (0.3-0.7) g: (80-120) mL.
[0023] Furthermore, the modified graphene oxide is prepared by mixing a manganese-cerium composite precursor with graphene oxide and subjecting the mixture to a two-step hydrothermal treatment.
[0024] Furthermore, the diameter of graphene oxide is 0.1-2 μm.
[0025] Furthermore, two-step hydrothermal treatment is performed: the first step of hydrothermal treatment is performed at a temperature of 170-190°C for 1-3 h, and the second step of hydrothermal treatment is performed at a temperature of 250-350°C for 1-2 h.
[0026] Further, the modified graphene oxide is specifically prepared by the following steps: B1. Add manganese chloride tetrahydrate to deionized water, stir until dissolved, add cerium dioxide powder and urea, stir at 300-400 rpm for 1-2 hours to obtain a manganese-cerium composite precursor.
[0027] B2. The manganese-cerium composite precursor and graphene oxide were mixed, stirred at 300 rpm for 30 minutes, placed in a hydrothermal reactor for hydrothermal reaction, cooled to room temperature, filtered to obtain a precipitate, washed the precipitate with deionized water three times, and dried in an oven at 70°C for 10 minutes to obtain modified graphene oxide.
[0028] Furthermore, in the above reaction process B1, manganese chloride tetrahydrate is added to deionized water to form a manganese precursor, and cerium dioxide and urea are added to the manganese precursor so that cerium dioxide and urea are dissolved in the manganese precursor to form a manganese-cerium composite precursor.
[0029] Furthermore, in the above-mentioned B2 reaction process, the graphene oxide nanosheets have a high specific surface area, and the oxygen-containing functional groups on the surface can be combined with the manganese ions and cerium ions in the manganese-cerium composite precursor through chemical bonds, so that the manganese-cerium composite precursor is deposited on the surface of the graphene oxide nanosheets. The urea contained in the manganese-cerium composite precursor acts as a precipitant, which can complex with the manganese ions and cerium ions on the surface of the graphene oxide nanosheets to form hydroxides. After two-step hydrothermal treatment, the hydrothermal treatment is carried out at 180°C for 2h, and the cerium hydroxide is thermally decomposed to form nano-cerium dioxide on the graphene oxide nanosheets. The temperature is raised to 300°C, and the hydrothermal treatment is continued. The manganese hydroxide decomposes to form nano-manganese dioxide, which is deposited on the graphene oxide nanosheets or nano-cerium dioxide, thereby forming a concave-convex structure on the surface of the graphene oxide nanosheets.
[0030] Furthermore, in step B1, the dosage ratio of manganese chloride tetrahydrate, deionized water, cerium dioxide powder and urea is (11.6-12) g: (80-120) mL: (6-6.4) g: (2-3) g.
[0031] Furthermore, in step B2, the mass ratio of manganese-cerium composite precursor to graphene oxide is (45-55):(0.5-1.5).
[0032] Furthermore, the modified glass fiber is prepared by mixing acid-etched glass fiber, oxalic acid and melamine and then calcining.
[0033] Furthermore, the calcination temperature is 550-650° C., and the calcination time is 1-3 h.
[0034] Furthermore, the glass fiber has a diameter of 50-100 nm and a length of 2-5 μm.
[0035] Further, the modified glass fiber is specifically prepared by the following steps: C1. Add the glass fiber to 1 mol / L hydrochloric acid, stir at 40°C for 30 min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain acid-etched glass fiber.
[0036] C2. Mix the acid-etched glass fiber with oxalic acid and deionized water, add hydrochloric acid with a concentration of 1 mol / L, stir at 80°C for 2 hours, filter, and dry in an oven at 120°C for 10 minutes to obtain a mixture, add the mixture and melamine powder into ethanol, stir evenly, filter, place in a muffle furnace, calcine at 600°C for 2 hours, and cool to room temperature to obtain modified glass fiber.
[0037] Furthermore, during the C1 reaction, the glass fiber is acid-etched to remove organic matter and impurities on the surface or in the pores of the glass fiber, thereby increasing the roughness of the glass fiber surface, improving the surface wettability and bonding strength with oxalic acid and melamine, and facilitating the formation of nitrogen oxide dopants on the glass fiber surface.
[0038] Furthermore, during the above-mentioned C2 reaction process, the oxygen-containing functional groups contained on the surface of the acid-etched glass fiber can be combined with the carboxyl groups in the oxalic acid through chemical bonds, and the ester groups and carboxyl groups in the oxalic acid can be combined with the nitrogen groups in the melamine, so that the melamine can act evenly on the surface of the glass fiber, which is beneficial to the synthesis of evenly distributed nitrogen elements on the surface of the glass fiber.
[0039] Furthermore, in step C1, the ratio of glass fiber to hydrochloric acid is (0.5-0.9) g:(45-55) mL.
[0040] Furthermore, in step C2, the ratio of acid-etched glass fiber, oxalic acid, deionized water, and hydrochloric acid is (0.5-1.5) g: (0.3-0.7) g: (80-120) mL: (0.05-0.15) mL.
[0041] Furthermore, in step C2, the ratio of the mixture, melamine powder and ethanol is (0.5-1.5) g: (0.1-0.3) g: (15-25) mL.
[0042] The present invention also provides a low-temperature denitration process, comprising the following steps: The denitration catalyst is filled into the denitration reactor, and the flue gas is passed into the heat exchanger. After the temperature is controlled at 180-250°C, it is passed into the denitration reactor filled with the denitration catalyst, and a mixed gas of ammonia is passed in for low-temperature denitration treatment.
[0043] Furthermore, the flue gas flow rate is 5-10 m / s, and the low-temperature denitrification treatment time is 10-30 s.
[0044] Furthermore, NO in flue gas x The concentration of SO is 3000-4500mg / Nm x The concentration is 3700-4500mg / Nm.
[0045] Furthermore, the ammonia gas mixture is a mixture of ammonia and air, wherein the volume concentration of ammonia in the ammonia gas mixture is 5-8%.
[0046] Furthermore, compared with the prior art, the present invention has the following beneficial effects: (1) In the technical scheme of the present invention, a manganese-cerium composite precursor is mixed with graphene oxide and subjected to hydrothermal treatment to form nano-cerium dioxide and nano-manganese dioxide which can be deposited on graphene oxide nanosheets, thereby forming a concave-convex structure on the surface of the graphene oxide nanosheets. The graphene oxide nanosheets serve as carriers of nano-cerium dioxide and nano-manganese dioxide. On the one hand, nano-cerium dioxide and nano-manganese dioxide are synthesized in situ on the surface of the graphene oxide nanosheets to avoid the shedding of active components of nano-cerium dioxide and nano-manganese dioxide, thereby affecting the denitration performance. On the other hand, the concave-convex structure is formed on the surface of the graphene oxide nanosheets, thereby increasing the number of active sites of the denitration catalyst. In addition, the formed nano-cerium dioxide and nano-manganese dioxide can oxidize nitrogen oxides to form nitrates, which are further oxidized to nitrates or (and) nitrites. Nitrites react rapidly with nitrates to form NO2, which has a high denitration efficiency, thereby effectively improving the denitration performance of the catalyst.
[0047] (2) In the technical scheme of the present invention, a polydopamine layer is formed on the surface of the zirconia nanosheets, which gives the zirconia nanosheets excellent adhesion, thereby obtaining dopamine surface-modified zirconia nanosheets. The modified graphene oxide is mixed with the dopamine surface-modified zirconia nanosheets, and the surface of the dopamine surface-modified zirconia nanosheets contains a polydopamine layer. The dopamine surface-modified zirconia nanosheets can be deposited on the surface of the modified graphene oxide to form a sandwich structure, so that the active components of nano-cerium dioxide and nano-manganese dioxide exist between the interlayers, giving the interlayers a larger pore structure and increasing the contact area with nitrogen oxides. The formed sandwich structure further increases the protective effect on the active components of nano-cerium dioxide and nano-manganese dioxide, avoids the shedding of the active components, and prolongs the service life of the denitration catalyst. In addition, the interlayer channels of the nano-layered structure help the diffusion and transmission of nitrogen oxides and reactants in the denitration catalyst, reducing the blockage of pores. The graphene oxide and zirconia nanosheets provide a variety of active sites in the denitration reaction, thereby improving the catalytic performance.
[0048] (3) In the technical solution of the present invention, the acid-etched glass fiber is mixed with oxalic acid and melamine, and after calcination, a large amount of uniformly distributed nitrogen elements are formed on the surface of the glass fiber. The formed nitrogen elements promote the adsorption and oxidation ability of nitrogen oxides on the surface of the denitration catalyst, and improve the catalytic reduction of the denitration catalyst at low temperatures. In addition, the modified glass fiber is added to the nickel foam. The excellent aspect ratio of the modified glass fiber can absorb external stress, improve the compressive strength of the denitration catalyst, and avoid the porous structure of the denitration catalyst, which is easy to break under the action of external force, resulting in a decrease in denitration efficiency.
[0049] (4) In the technical solution of the present invention, the composite nanomaterial, modified glass fiber and deionized water are mixed to form a slurry, and the porous structure of the acid-treated nickel foam is filled with the slurry. After sintering, the composite nanomaterial and modified glass fiber are dispersed in the unique network structure of the nickel foam. The unique network structure of the nickel foam can inhibit the deposition of sulfate under the activity of the nickel foam, and has good anti-sulfur performance. In addition, the layered structure of the composite nanomaterial can also absorb external stress, serving as a supporting skeleton of the nickel foam, thereby improving the compressive strength of the nickel foam denitrification catalyst, and has a synergistic effect with the modified glass fiber in improving the compressive strength of the denitrification catalyst. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The raw materials used in the embodiments of the present invention are as follows: Manganese chloride tetrahydrate (purity 99%, Shanghai Beinuo Biotechnology Co., Ltd.); cerium dioxide (purity 99%, Jinan Huijinchuan Trading Co., Ltd.); urea (Jiangsu Jiaren Chemical Co., Ltd.); dopamine (purity 98%, Shenzhen Hengfeng Wanda Pharmaceutical Technology Co., Ltd.); Tris-HCl buffer (pH 8.5, Wuhan Desheng Biochemical Technology Co., Ltd.); oxalic acid (purity 99.6%, Wuhan Jiyesheng Chemical Co., Ltd.); melamine (purity 99.8%, Xuzhou Deyang Trading Co., Ltd.).
[0052] The diameter of graphene oxide is 0.1-2μm, Shanghai Hanlang New Material Technology Co., Ltd.
[0053] The diameter of zirconia nanosheets is 0.1-1μm, Yunyan New Materials (Shanghai) Co., Ltd.
[0054] The porosity of nickel foam is 94-96%, the pore size is 0.1-0.2mm, and the volume density is 0.4-0.6g / cm 3 , Kunshan Guangshengjia New Materials Co., Ltd.
[0055] Embodiment 1, the composite nano material is prepared by the following steps: A1. Add 11.8g of manganese chloride tetrahydrate to 100mL of deionized water, stir until dissolved, add 6.2g of cerium dioxide powder and 2.5g of urea, stir at 350rpm for 1.5h to obtain a manganese-cerium composite precursor. Mix 50g of the manganese-cerium composite precursor with 1g of graphene oxide, stir and mix at 300rpm for 30min, place in a hydrothermal reactor, perform a hydrothermal reaction, cool to room temperature, filter, obtain a precipitate, wash the precipitate with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified graphene oxide.
[0056] A2. Add 2.5 g of zirconium oxide nanosheets to 50 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.7 g of dopamine, stir for reaction, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain dopamine surface-modified zirconium oxide nanosheets.
[0057] A3. Add 0.2 g of modified graphene oxide and 0.5 g of dopamine surface-modified zirconia nanosheets into 100 mL of deionized water, ultrasonically treat at 40 Hz for 30 min, filter, wash with deionized water three times, and dry in an oven at 80°C for 10 min to obtain a composite nanomaterial.
[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified graphene oxide is replaced by graphene oxide, and the remaining steps and raw materials are the same as Example 1.
[0059] A1. Add 2.5 g of zirconium oxide nanosheets to 50 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.7 g of dopamine, stir for reaction, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain dopamine surface-modified zirconium oxide nanosheets.
[0060] A2. 0.2 g of graphene oxide and 0.5 g of dopamine surface-modified zirconium oxide nanosheets were added to 100 mL of deionized water, ultrasonically treated at 40 Hz for 30 min, filtered, washed with deionized water three times, and dried in an oven at 80°C for 10 min to obtain a composite nanomaterial.
[0061] Comparative Example 2 The difference between this comparative example and Example 1 is that the dopamine surface-modified zirconium oxide nanosheets are replaced by zirconium oxide nanosheets, and the remaining steps and raw materials are the same as Example 1.
[0062] A1. Add 11.8g of manganese chloride tetrahydrate to 100mL of deionized water, stir until dissolved, add 6.2g of cerium dioxide powder and 2.5g of urea, stir at 350rpm for 1.5h to obtain a manganese-cerium composite precursor. Mix 50g of the manganese-cerium composite precursor with 1g of graphene oxide, stir and mix at 300rpm for 30min, place in a hydrothermal reactor, perform a hydrothermal reaction, cool to room temperature, filter, obtain a precipitate, wash the precipitate with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified graphene oxide.
[0063] A2. 0.2 g of modified graphene oxide and 0.5 g of zirconium oxide nanosheets were added to 100 mL of deionized water, ultrasonically treated at 40 Hz for 30 min, filtered, washed with deionized water three times, and dried in an oven at 80°C for 10 min to obtain a composite nanomaterial.
[0064] Comparative Example 3 The difference between this comparative example and Example 1 is that dopamine is not added to surface-modify the zirconium oxide nanosheets, and the remaining steps and raw materials are the same as those of Example 1.
[0065] 11.8 g of manganese chloride tetrahydrate was added to 100 mL of deionized water, stirred until dissolved, 6.2 g of cerium dioxide powder and 2.5 g of urea were added, and stirred at 350 rpm for 1.5 h to obtain a manganese-cerium composite precursor. 50 g of the manganese-cerium composite precursor was mixed with 1 g of graphene oxide, stirred at 300 rpm for 30 min, placed in a hydrothermal reactor, subjected to a hydrothermal reaction, cooled to room temperature, filtered, and a precipitate was obtained. The precipitate was washed 3 times with deionized water and dried in an oven at 70 ° C for 10 min to obtain a composite nanomaterial.
[0066] Embodiment 2, the modified glass fiber is specifically prepared by the following steps: C1. Add 0.7 g of glass fiber to 50 mL of 1 mol / L hydrochloric acid, stir at 40°C for 30 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain acid-etched glass fiber.
[0067] C2. Mix 1 g of acid-etched glass fiber with 0.5 g of oxalic acid and 100 mL of deionized water, add 0.1 mL of 1 mol / L hydrochloric acid, stir at 80 ° C for 2 h, filter, and dry in an oven at 120 ° C for 10 min to obtain a mixture, add 1 g of the mixture and 0.2 g of melamine powder to 20 mL of ethanol, stir evenly, filter, place in a muffle furnace, calcine at 600 ° C for 2 h, and cool to room temperature to obtain modified glass fiber.
[0068] Comparative Example 4 The difference between this comparative example and Example 2 is that oxalic acid and melamine are not added, and the remaining steps and raw materials are the same as those of Example 2.
[0069] 0.7 g of glass fiber was added to 50 mL of 1 mol / L hydrochloric acid, stirred at 40° C. for 30 min, filtered, washed with deionized water 3 times, and dried in an oven at 70° C. for 10 min to obtain modified glass fiber.
[0070] Comparative Example 5 The difference between this comparative example and Example 2 is that the acid-etched glass fiber is replaced by glass fiber, and the remaining steps and raw materials are the same as Example 2.
[0071] Mix 1 g of glass fiber with 0.5 g of oxalic acid and 100 mL of deionized water, add 0.1 mL of 1 mol / L hydrochloric acid, stir at 80 ° C for 2 h, filter, and dry in an oven at 120 ° C for 10 min to obtain a mixture, add 1 g of the mixture and 0.2 g of melamine powder to 20 mL of ethanol, stir evenly, filter, place in a muffle furnace, calcine at 600 ° C for 2 h, and cool to room temperature to obtain modified glass fiber.
[0072] Embodiment 3, a method for preparing a denitration catalyst, comprising the following steps: S1. The composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water are mixed and stirred to obtain a slurry, wherein the amount ratio of the composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water is 3g:1g:80mL.
[0073] S2. Soak the nickel foam in an acetone solution for 15 minutes, take it out, wash it three times with deionized water, soak it in 3 mol / L dilute hydrochloric acid for 15 minutes, take it out, wash it three times with deionized water, and dry it in an oven at 60°C for 10 minutes to obtain acid-treated nickel foam.
[0074] S3. 30 g of acid-treated nickel foam was impregnated into 50 g of slurry, stirred at 400 rpm for 5 h, washed with deionized water 3 times, dried in an oven at 70° C. for 1 h, sintered in a sintering furnace, and cooled to room temperature to obtain a denitrification catalyst, wherein the sintering temperature was 350° C. and the sintering time was 3 h.
[0075] Embodiment 4, a method for preparing a denitration catalyst, comprising the following steps: S1. The composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water are mixed and stirred to obtain a slurry, wherein the amount ratio of the composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water is 3.5g:1.5g:100mL.
[0076] S2. Soak the nickel foam in an acetone solution for 15 minutes, take it out, wash it three times with deionized water, soak it in 3 mol / L dilute hydrochloric acid for 15 minutes, take it out, wash it three times with deionized water, and dry it in an oven at 60°C for 10 minutes to obtain acid-treated nickel foam.
[0077] S3. Impregnate 35g of acid-treated nickel foam into 55g of slurry, stir at 400-500rpm for 5-6h, filter, wash with deionized water 3 times, dry in an oven at 80°C for 2h, place in a sintering furnace for sintering, and cool to room temperature to obtain a denitrification catalyst, wherein the sintering temperature is 400°C and the sintering time is 3.5h.
[0078] Embodiment 5, a method for preparing a denitration catalyst, comprising the following steps: S1. The composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water are mixed and stirred to obtain a slurry, wherein the amount ratio of the composite nanomaterial prepared in Example 1, the modified glass fiber prepared in Example 2, and deionized water is 4g:2g:120mL.
[0079] S2. Soak the nickel foam in an acetone solution for 15 minutes, take it out, wash it three times with deionized water, soak it in 3 mol / L dilute hydrochloric acid for 15 minutes, take it out, wash it three times with deionized water, and dry it in an oven at 60°C for 10 minutes to obtain acid-treated nickel foam.
[0080] S3. Impregnate 40g of acid-treated nickel foam into 60g of slurry, stir at 400-500rpm for 5-6h, filter, wash with deionized water 3 times, dry in an oven at 90°C for 3h, place in a sintering furnace for sintering, and cool to room temperature to obtain a denitrification catalyst, wherein the sintering temperature is 450°C and the sintering time is 4h.
[0081] Comparative Example 6 The difference between this comparative example and Example 4 is that the composite nanomaterial prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.
[0082] Comparative Example 7 The difference between this comparative example and Example 4 is that the composite nanomaterial prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.
[0083] Comparative Example 8 The difference between this comparative example and Example 4 is that the composite nanomaterial prepared in Example 1 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.
[0084] Comparative Example 9 The difference between this comparative example and Example 4 is that the modified glass fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.
[0085] Comparative Example 10 The difference between this comparative example and Example 4 is that the modified glass fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 5, and the remaining steps are synchronized with Example 4.
[0086] The performance of the denitration catalysts prepared in Examples 3-5 and Comparative Examples 6-10 was tested; A low-temperature denitration process comprises the following steps: The denitration catalyst is filled into the denitration reactor, and the flue gas is passed into the heat exchanger. After the temperature is controlled at 180, 210, and 240°C, it is passed into the denitration reactor filled with the denitration catalyst and ammonia mixed gas is passed in for low-temperature denitration treatment. The flue gas flow rate is 8m / s, and the low-temperature denitration treatment time is 20s. x The concentration is 4000mg / Nm, SO x The concentration of ammonia is 4200 mg / Nm; the mixed gas of ammonia is a mixture of ammonia and air, wherein the volume concentration of ammonia in the mixed gas of ammonia is 6%.
[0087] The gas after the reaction is then measured by an online gas analyzer and recorded in a computer.
[0088] Denitrification efficiency test: Denitrification efficiency = [(C0-C) / C0] × 100%. C0 is NO x Initial concentration, C is the NO in the treated gas x concentration.
[0089] Mechanical strength test: The prepared denitration catalyst was placed in clean water, soaked for 30 minutes, taken out, and dried at 120°C. The dried denitration catalyst was placed in a sulfuric acid solution with a pH of 2, soaked for 30 minutes, taken out, dried at 120°C, and calcined in a muffle furnace at 500°C for 5 hours. According to the national standard GB / T 1964-2023 "Test method for room temperature compression strength of porous ceramics", the longitudinal strength and axial strength were measured; the results are shown in Table 1 below: Table 1
[0090] It can be seen from the data in Table 1 that in Comparative Example 6, the modified graphene oxide is replaced by a composite nanomaterial prepared by graphene oxide, and the denitration efficiency and mechanical properties are reduced. This may be because nano-cerium dioxide and nano-manganese dioxide are synthesized on the graphene oxide nanosheets, and the sandwich structure formed with the dopamine surface-modified zirconium oxide nanosheets can absorb external stress and improve the compressive strength of the denitration catalyst. The composite nanomaterial prepared in Comparative Example 6 lacks nano-cerium dioxide and nano-manganese dioxide, and cannot achieve this effect. Therefore, the denitration efficiency and mechanical properties are reduced.
[0091] In Comparative Example 7, the dopamine surface-modified zirconia nanosheets are replaced with a composite nanomaterial prepared from zirconia nanosheets to prepare a denitration catalyst, and its denitration efficiency and mechanical properties are reduced. This may be because a polydopamine layer is formed on the surface of the zirconia nanosheets, which can form a sandwich structure with the modified graphene oxide, giving the layers a larger pore structure and increasing the contact area with nitrogen oxides. The formed sandwich structure further increases the protection of the active components of nano-cerium dioxide and nano-manganese dioxide, avoiding the shedding of the active components. However, the zirconia nanosheets in Comparative Example 7 lack the adhesion of the polydopamine layer and cannot achieve this effect. Therefore, the denitration efficiency and mechanical properties are reduced.
[0092] In Comparative Example 8, the composite nanomaterial prepared by adding dopamine surface-modified zirconia nanosheets was used to prepare a denitration catalyst, and its denitration efficiency and mechanical properties decreased. This may be because the dopamine surface-modified zirconia nanosheets were deposited on the surface of the modified graphene oxide, and its layered structure was able to absorb external stress, serving as a supporting skeleton for the nickel foam, thereby improving the compressive strength of the nickel foam denitration catalyst. However, Comparative Example 8 lacked a composite layered structure and could not achieve this effect, so the denitration efficiency and mechanical properties decreased.
[0093] In comparative example 9, the modified glass fiber prepared without adding oxalic acid and melamine was used to prepare the denitration catalyst, and its denitration efficiency decreased. This may be because a large amount of uniformly distributed nitrogen elements were formed on the surface of the glass fiber. The formed nitrogen elements promoted the adsorption and oxidation ability of nitrogen oxides on the surface of the denitration catalyst, and improved the catalytic reduction ability of the denitration catalyst at low temperatures. However, the modified glass fiber of comparative example 8 lacked nitrogen elements and could not achieve this effect, so the denitration efficiency decreased.
[0094] In Comparative Example 10, the acid-etched glass fiber is replaced with modified glass fiber prepared from glass fiber, and the denitrification efficiency is reduced. This may be because the acid-etched glass fiber can remove organic matter and impurities on the surface or in the pores of the glass fiber, increase the roughness of the glass fiber surface, and improve the surface wettability and bonding strength with oxalic acid and melamine, which is conducive to the formation of nitrogen oxides on the surface of the glass fiber, thereby improving the denitrification efficiency.
[0095] The data in Table 1 show that the denitration catalysts prepared in Examples 3-5 meet the test performance requirements, while the denitration catalysts prepared in Comparative Examples 6-10 do not meet the performance requirements, indicating that the denitration catalysts prepared in the present invention have good low-temperature denitration performance and mechanical strength.
[0096] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0097] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the defined scope, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a denitration catalyst, characterized in that: The following steps are involved: S1. Mixing the composite nanomaterial, modified glass fiber and deionized water, stirring to obtain a slurry; The usage ratio of the composite nanomaterial, modified glass fiber and deionized water is (3-4) g: (1-2) g: (80-120) mL; S2. The acid-treated nickel foam is impregnated into the slurry, stirred at 400-500 rpm for 5-6 hours, filtered, washed, dried, sintered, and cooled to room temperature to obtain a denitration catalyst; The composite nanomaterial is prepared by modifying the surface of zirconium oxide nanosheets with dopamine and then mixing with modified graphene oxide; The modified graphene oxide is prepared by mixing a manganese-cerium composite precursor with graphene oxide and subjecting the mixture to a two-step hydrothermal treatment; The modified glass fiber is prepared by mixing acid-etched glass fiber, oxalic acid and melamine and then calcining.
2. The method for preparing a denitration catalyst according to claim 1, characterized in that: In step S2, the mass ratio of the acid-treated nickel foam to the slurry is (30-40):(50-60).
3. The method for preparing a denitration catalyst according to claim 1, characterized in that: In step S2, the sintering temperature is 350-450°C, and the sintering time is 3-4h.
4. The method for preparing a denitration catalyst according to claim 1, characterized in that: The two-step hydrothermal treatment: the first step of the hydrothermal treatment temperature is 170-190°C, the time is 1-3h, and the second step of the hydrothermal treatment temperature is 250-350°C, the time is 1-2h.
5. The method for preparing a denitration catalyst according to claim 1, characterized in that: The manganese-cerium composite precursor is specifically prepared by the following steps: Manganese chloride tetrahydrate is added to deionized water, stirred until dissolved, cerium dioxide powder and urea are added, and stirred at 300-400 rpm for 1-2 hours to obtain a manganese-cerium composite precursor.
6. The method for preparing a denitration catalyst according to claim 1, characterized in that: The diameter of the graphene oxide is 0.1-2 μm; the diameter of the zirconium oxide nanosheet is 0.1-1 μm.
7. The method for preparing a denitration catalyst according to claim 1, characterized in that: The acid-etched glass fiber is specifically prepared by the following steps: adding the glass fiber into hydrochloric acid with a concentration of 0.5-1.5 mol / L, stirring at 30-50° C. for 25-35 minutes, filtering, washing, and drying to obtain the acid-etched glass fiber.
8. The method for preparing a denitration catalyst according to claim 1, characterized in that: The calcination temperature is 550-650° C., and the calcination time is 1-3 hours.
9. A denitration catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. A low-temperature denitration process using a denitration catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The steps include: The denitration catalyst is filled into the denitration reactor, and the flue gas is passed into the heat exchanger. After the temperature is controlled at 180-250°C, it is passed into the denitration reactor filled with the denitration catalyst, and a mixed gas of ammonia is passed in for low-temperature denitration treatment.
Citation Information
Patent Citations
Al2O3 nanosheet reinforced ZrO2 tritium-resistant coating and preparation method thereof
CN114427086A
Electrically heatable denitration catalyst and application method thereof
CN117643876A
Foam metal-based catalyst for denitration at ultralow temperature and preparation method of foam metal-based catalyst
CN117643911A
Cited By
Preparation method of SCR (Selective Catalytic Reduction) denitration catalyst
CN119425816A
